Tunable Structured MXenes With Modulated Atomic Environments: A Powerful New Platform for Electrocatalytic Energy Conversion. Issue 41 (21st August 2022) - Xiao, Sutong; Zheng, Yijuan; Wu, Xizheng; Zhou, Mi; Rong, Xiao; Wang, Liyun; Tang, Yuanjiao; Liu, Xikui; Qiu, Li; Cheng, Chong
Abstract: Owing to their rich surface chemistry, high conductivity, tunable bandgap, and thermal stability, structured 2D transition‐metal carbides, nitrides, and carbonitrides (MXenes) with modulated atomic environments have emerged as efficient electrochemical energy conversion systems in the past decade. Herein, the most recent advances in the engineering of tunable structured MXenes as a powerful new platform for electrocatalytic energy conversion are comprehensively summarized. First, the state‐of‐the‐art synthetic and processing methods, tunable nanostructures, electronic properties, and modulation principles of engineering MXene‐derived nanoarchitectures are focused on. The current breakthroughs in the design of catalytic centers, atomic environments, and the corresponding structure–performance correlations, including termination engineering, heteroatom doping, defect engineering, heterojunctions, and alloying, are discussed. Furthermore, representative electrocatalytic applications of structured MXenes in energy conversion systems are also summarized. Finally, the challenges in and prospects for constructing MXene‐based electrocatalytic materials are also discussed. This review provides a leading‐edge understanding of the engineering of various MXene‐based electrocatalysts and offers theoretical and experimental guidance for prospective studies, thereby promoting the practical applications of tunable structured MXenes in electrocatalytic energy conversion systems. Abstract : The cutting‐edge advances in engineering tunable structured MXenes as a new powerful platform for electrocatalytic energy conversion are comprehensively summarized in this review, including state‐of‐the‐art synthetic strategies, latest breakthroughs in nanostructure and catalytic center modulation, representative electrocatalytic applications, and the corresponding prospects and challenges for theoretical and experimental guidance toward the promotion of their future application in electrocatalysis.